Fostering Europe’s Future Physician-Scientists: An Interview with European MD/PhD Association Chairman Dr. André dos Santos Rocha - Paul M. Ryan; André dos Santos Rocha (International Journal of Medical Students, 2020)
Dr. André dos Santos Rocha is a Resident Physician in Intensive Care Medicine & Anaesthesiology and a current MD-PhD student in the Department of Acute Medicine at the University of Geneva. In parallel, he is also the current Chairman of the European MD/PhD Association (EMPA), a role in which he coordinates a diverse group of highly-driven MD-PhD students. EMPA is a not-for-profit organisation which was founded with the central aims of bringing together MD-PhDs from across Europe, fostering a comfortable setting for networking, promotion of European scientific collaborations and support for research and mobility of European MD-PhD students. One of the main medium through which EMPA achieves a number of these lofty goals is their annual conference, which is typically held in conjunction with one of the national associations. I met with André after the recent European and Swiss MD-PhD Conference in Geneva to discuss his experience in this role and what the future holds for EMPA.